Modeling MELAS-associated cardiac defects using patient-specific iPSC-derived cardiomyocytes and cardiac organoids - Phua, Qian Hua (2018)
Mitochondrial diseases are a diverse family of maternally-inherited disorders that often result from mitochondrial DNA (mtDNA) mutations. These disorders are mostly heterogeneous and manifest as a broad spectrum of clinical phenotypes among patients. In this study, we will be utilising patient-specific induced pluripotent stem cells (iPSCs) generated from a patient with Mitochondrial encephalomyopathy, Lactic acidosis and Stroke-like symptoms (MELAS) syndrome, a mitochondrial disease caused by m.3243A>G mutation. The primary objective of our study is to generate a reliable in vitro model for investigating the underlying molecular mechanisms that contribute to the pathogenesis of cardiomyopathies in MELAS. In this study, our iPSC-based in vitro model presented novel evidences showing that mitochondrial perturbations found in MELAS affects cardiomyocytes (CMs) differentiation and maturation. Mild mitochondrial aberrations such as mitochondria dynamic disequilibrium and abnormal increase in mitochondria numbers were also being recapitulated in our model. In addition, pronounced metabolic dysfunctions were observed in MELAS CMs and cardiac organoids (COs). Lastly, we were able to demonstrate the prevalence of some cardiac pathologies in the 3D-based organoid model. Overall, we were able to successfully model MELAS-associated cardiomyopathies in vitro, which has potential in bringing great strides into advancing the understanding of MELAS syndrome and facilitate therapeutic discoveries for these patients.